Techno-economic assessment of decarbonization pathways for a gas to liquid facility: a review - Awani, Kelvin; Hanak, Dawid P.; Kumar, Vinod; Nabavi, Seyed Ali (Elsevier, 2024)
An overview of gas-to-liquid (GTL) fuels which explores various approaches to decarbonizing gas-to-liquid facilities is here presented. The review discusses optimization of heat integration in the air separation unit (ASU) to reduce energy requirements, the implementation of loop reactor concepts and gas-to-liquid looping to decrease CO2 emissions, the use of amine absorber/stripper systems and reforming configurations to enhance CO2 consumption, and the utilization of staged Fischer-Tropsch (FT) reactors to improve CO2 recovery and tail gas recycle performance. The integration of gas-to-liquid processes with power plants and ammonia/urea synthesis plants is also examined as a means of utilizing CO2 and improving process economics. The review further highlights the potential of power-based oxygen and hydrogen in biomass-to-liquid (BtL) processes for higher carbon efficiency and reduced greenhouse gas emissions. Techno-economic assessments were reviewed to evaluate the feasibility and profitability of different decarbonization pathways, considering factors such as capital and operational expenditures, product prices, internal rates of return (IRR), and carbon efficiency. The review identified challenges in water treatment and hydrogen purification for gas-to-liquid and small-scale gas-to-liquid plants. The findings emphasized the need for a comprehensive framework to mitigate CO2 emissions from gas-to-liquid facilities and facilitate the effective decarbonization of the oil and gas industry.
Keywords: 4004 Chemical Engineering; 40 Engineering; 13 Climate Action; 7 Affordable and Clean Energy; Techno-economic; Decarbonization; Gas-to-liquid; Biogas Utilisation; Sustainable aviation fuel